2012
DOI: 10.3329/bjz.v39i2.10587
|View full text |Cite
|
Sign up to set email alerts
|

Study of fecundity and induced breeding of <i>Mystus vittatus</i>

Abstract: Abstract:The present study deals with the estimation of fecundity and induced breeding of Mystus vittatus by using carp PG hormone. Four different doses were tested, viz. 6, 8, 10 and 12 mg/kg body weight for female and 3, 4, 5 and 6 mg/kg body weight for male. For each dose, three different sex ratios were maintained, viz. 1♂: 1♀, 2♂: 1♀ and 3♂: 2♀. The hormone doses 8 mg/kg for female and 4 mg/kg for male provided the best result in the sex ratio 2♂: 1♀. This treatment combination revealed 80% fertilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 1 publication
3
13
0
Order By: Relevance
“…The maximum absolute fecundity (12338.57 ± 1241.04) was found in the length group of 11.5-14 cm and the minimum (6965±889.38) in 6.5-9.0 cm. The fecundity was found increased with the increase in length of the M. dibrugarensis that similar with the findings of Azadi et al (1987), Siddique et al Islam et al (2011) and Gupta (2013). Monthly, highest absolute fecundity (7026±2200) and relative fecundity (830.2 ±167.8) was found in April and lowest absolute fecundity (411±154.7) and relative fecundity (44 ± 22.7) in August.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The maximum absolute fecundity (12338.57 ± 1241.04) was found in the length group of 11.5-14 cm and the minimum (6965±889.38) in 6.5-9.0 cm. The fecundity was found increased with the increase in length of the M. dibrugarensis that similar with the findings of Azadi et al (1987), Siddique et al Islam et al (2011) and Gupta (2013). Monthly, highest absolute fecundity (7026±2200) and relative fecundity (830.2 ±167.8) was found in April and lowest absolute fecundity (411±154.7) and relative fecundity (44 ± 22.7) in August.…”
Section: Resultssupporting
confidence: 89%
“…male was observed more actively involved in courtship. The same phenomenon was also reported by Alam et al (2006) and Islam et al (2011). Spawning occurred after 2-3 hr.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…But hatching was occurred in confined water. Islam et al [4] observed 57-80% fertilization rate and 32-56% hatching rate in case of Mystus vittatus with different doses of hormone ranging from 4-6 mg/kg in male and 8-12 mg/kg in female. Ray, 2005 found 90% fertilization rate that yielded hatchings about 80% of fertilized eggs in Mystus gulio.…”
Section: Experimental Lay-outmentioning
confidence: 99%
“…However, scientific information on the spawning season and induced breeding of Mystus species are limited in literature. The few published works available are Ray [3][4][5][6][7]. Up to now there is no information on the reproductive biology and captive breeding of Mystus dibrugarensis.…”
Section: Introductionmentioning
confidence: 99%